Marine algae of St. Martin's Island, Bangladesh. VIII. new records of red algae (Rhodophyceae) - Islam, Shahima; Aziz, Abdul; Chowdhury, Abdullah Harun (Bangladesh Journal of Botany, 2010)
Ceramium brevizonatum var. caraibica Peter. et Børg., Dasya corymbifera J. Ag., Dudresnaya hawaiiensis R.K.S. Lee, Chrysymenia agardhii Harv. and Hypnea boergesenii Tanaka are recorded and described for the first time from the St. Martin's Island, Cox's Bazar, Bangladesh. Key words: Seaweeds; Red algae; Dudresnaya hawaiiensis; St. Martin's Island; Bangladesh DOI: 10.3329/bjb.v39i1.5531 Bangladesh J. Bot. 39(1): 87-96, 2010 (June)